Computational insight into the catalytic implication of head/tail-first orientation of arachidonic acid in human 5-lipoxygenase: consequences for the positional specificity of oxygenation. Issue 33 (4th August 2016) - Saura, Patricia; Maréchal, Jean-Didier; Masgrau, Laura; Lluch, José M.; González-Lafont, Àngels
Abstract : Using a multi-scale approach to search for the arachidonic acid binding modes that determine the catalytic specificity of human 5-LOX. Abstract : In the present work we have combined homology modeling, protein–ligand dockings, quantum mechanics/molecular mechanics calculations and molecular dynamics simulations to generate human 5-lipoxygenase (5-LOX):arachidonic acid (AA) complexes consistent with the 5-lipoxygenating activity (which implies hydrogen abstraction at the C7 position). Our results suggest that both the holo and the apo forms of human Stable 5-LOX could accommodate AA in a productive form for 5-lipoxygenation. The former, in a tail-first orientation, with the AA carboxylate end interacting with Lys409, gives the desired structures with C7 close to the Fe–OH − cofactor and suitable barrier heights for H7 abstraction. Only when using the apo form structure, a head-first orientation with the AA carboxylate close to His600 (a residue recently proposed as essential for AA positioning) is obtained in the docking calculations. However, the calculated barrier heights for this head-first orientation are in principle consistent with 5-LOX specificity, but also with 12/8 regioselectivity. Finally, long MD simulations give support to the recent hypothesis that the Phe177 + Tyr181 pair needs to close the active site access during the chemical reaction, and suggest that in the case of a head-first orientation Phe177 may be the residue interacting with the AA carboxylate.